The Impact of Foreign Remittance on Labor Productivity: A Case of Pakistan - Sattar, Nosheena; Sarwar, Kiran; Sajjad, Asma (Pakistan Journal of Humanities and Social Sciences, 2023)
This study attempts an empirical analysis of the effect of external remittance on labor productivity in Pakistan. This study used the time series data from 1975 to 2019. The Johanson co-integration approach and Trace and Maximum Lamda tests were used for economic analysis. The personal remittance, Gross Fixed Capital Formation (GFCF), and Officially Exchange Rate (PER) depicted significant and positive relationships and Foreign Direct Investment (FDI) and Trade both variables show positive but insignificant impacts on labor productivity. This study suggests that government should provide incentives for transfer payments to overseas Pakistanis for enhancing the remittances.